Pengenalan dan Pemetaan Lokasi Budidaya Perairan bagi Nelayan Desa Tandung menggunakan Unmanned Aerial Vehicle - Noor, Rahmat Januar; Mahfud, Chairul Rusyd; Nur, Fauzia; Nasyrah, Adiara Firdhita Alam (Yumary: Jurnal Pengabdian kepada Masyarakat, 2024)
Purpose: Improving community understanding of coastal spatial conditions, providing coastal spatial information in Tandung Village. Methodology: The location of the activity is in Tandung Village, Tinambung District, West Sulawesi. The activity went through the counseling stage, data recording using DJI 4 brand unmanned aerial vehicle (UAV) technology. The results of the data recording were processed using Agisoft software to produce a coastal spatial map. At the end of the activity, an evaluation was carried out to determine the achievement of the activity's objectives. Results: The community, especially the village government, began to recognize the use of technology for mapping that had never been seen directly before. The community was very enthusiastic when shown and given the opportunity to see the operation of drones for mapping. Information is available regarding the use of space activities on the coast of Tandung Village, especially related to the aquaculture activity and attracting the attention of the village government to initiate comprehensive spatial mapping in Tandung Village. Conclusions: Community service activities in Tandung Village have succeeded in increasing government and community understanding of UAV technology for mapping, which has encouraged initiatives to utilize drones in identifying land use for fisheries, agriculture, and plantations. Limitations: A fairly large coastal area requires time to record data using drones. Contribution: The results of the activity contribute to the provision of spatial data on coastal utilization in Tandung Village along with identification of potential that can be explored.